Analisis Pengukuran Kinerja Mesin Cetak Menggunakan Overall Equipment Effectiveness (OEE) Di CV Delimas - Endrawati, Budiani Fitria; Siti Zulaykha; Ismail, Andi Idhil (SPECTA Journal of Technology, 2024)
This study was conducted to assess the performance of a printing machine using Overall Equipment Effectiveness (OEE) calculations. The printing machine already meets the World Class standards with availability, performance, and quality metrics set at 85%. Achieving this standard is considered indicative of good machine performance according to these benchmarks. Recommendations for improvement include implementing machine maintenance management supported by routine maintenance by machine operators to minimize issues during production. The results from the OEE calculations show that the availability, performance, quality, and overall effectiveness of the machine have not reached or exceeded the World Class OEE standards. This has caused production delays due to the machine's low performance. The low performance is attributed to the fact that the printing machine operators at CV Delimas do not fully understand the machine's maintenance procedures. The performance metric for the printing machine at CV Delimas using OEE averages only 33%. This indicates that the machine's performance is significantly below the 95% standard.